Assessment of right ventricular systolic function in patients with chronic renal failure before and after hemodialysis by means of various echocardiographic modalities - Abdurrahman Akyüz; Abdulkadir Yıldız; Mehmet Ata Akıl; Mehmet Zihni Bilik; İsmail Yıldız; Zülfikar Yılmaz; Yaşar Yıldırım; Ümit İnci; Fetullah Kayan; Önder Bilge; Mehmet Sıddık Ülgen (Türk Kardiyoloji Derneği Arşivi, 2014)
Objectives: The goal of the study was to determine the effect of decreased preload on right ventricular systolic function, as measured by new and old echocardiographic parameters in chronic renal failure (CRF) patients. Study design: A total of 30 CRF patients (mean age 48 +- 15 years and 19 female) undergoing hemodialysis were included in the study. Echocardiography was used to determine left ventricular ejection fraction (LVEF), left atrial volume, right atrial area, right ventricular end-diastolic area, systolic pulmonary artery pressure, right ventricular fractional area change (RV FAC), right ventricular myocardial performance index (Tei index), right ventricular tissue Doppler S' (RV S') velocity, isovolumic myocardial acceleration (IVA), tricuspid annular plane systolic excursion (TAPSE) and right ventricular outflow tract systolic excursion (RVOT SE) before and after hemodialysis. Results: The RV S' velocity and RVOT SE parameters which are indicators of right ventricular systolic function did not change significantly after hemodialysis (p=0.919, p=0.186). However, the RV FAC, Tei index, IVA and TAPSE values were significantly increased (p<0.001 for all). TAPSE was found to be the only parameter that had a positive correlation with the amount of fluid removed (p=0.041 and r=0.375). Conclusions: Although RV S' velocity and RVOT SE, was found to be independent of preload, RV FAC, Tei index, IVA and TAPSE values were depend on the preload. In addition, TAPSE correlated with the amount of fluid removed.